A Study on Mobile Based Nbfc Catering Towards Rural Indian Customers – Special Reference To Igatpuri District in Maharastra - P. S. Aithal, Abdul Khalid (Journal of Neonatal Surgery, 2025)
Economic progress depends on the fact that people in emerging countries tend to view access to money as a fundamental right, akin to access to water, health, etc. This research aims to determine the impact and usage of mobile applications for financial services needed by rural clients. While having access to finance may be necessary for many households to escape poverty, it is not always necessary to have a relationship with a financial institution thanks to technology, data science, and machine learning-based rule engine platforms that are tightly coupled with mobile applications. This study aims to demonstrate how mobile applications are assisting rural Indians in spite of infrastructure issues including energy, transportation, and infrastructure becoming a barrier to meeting their financial demands. Due to the absence of major public sector banks in rural India, NBFCs (Non-Banking Financial Corporations) are forced to meet clients' financial demands because the availability of electricity and power systems is problematic. Mobility offers an alternative solution to this issue. The stack of mobility enters the scene and serves as a crucial link between the NBFC and the customer.